Pengelolaan Perkuliahan Mata Kuliah Bahasa Inggris Berbasis Laboratorium Di IKIP Veteran Semarang (Pawiyatan, 2015)
The purposes of this research are to describe (1) the layout of laboratory based English learning, (2) the material of laboratory-based English learning, (3) the lecturers’ and students’ activities in the laboratory-based English learning, and (4) the monitor and evaluation of laboratory-based English learning. This research is basically a qualitative research with ethnography research design. For the data collection techniques, it uses the observation, interview, and documentation. Data analysis technique uses an interactive model of analysis. Data validity uses a triangulation technique. The results of the research show that (1) the layout of laboratory-based English learning was created by giving attention to the need of students. The comfort condition was created by installation of Air Conditioner (AC) and sound system in the corner of the room. The tables and chairs were set by the formation of U letter and in each table was equipped with a headset for learning listening. (2) the material for the laboratory-based English learning consisted of the speaking and learning materials. The story telling material was considered to be a complicated and complex material. The delivery of material was done through demonstration method and used several media such as film, LCD, tape recorder. (3) lecturers and students were active in doing the laboratory-based English learning. Lecturers prepared learning activities and gave motivation in a guidance, reward and punishment. Through the incorporation of a variety of methods, lecturers were able to activate students such as doing the listening, speaking, discussion, and debating. Students had the opportunity to compete through a loud reading and a story telling. (4) monitoring and evaluation of the laboratory-based English learning were done during the learning process. The evaluation was done in written, spoken and practical tests to know students’ skill in listening and speaking. Students who excel got a reward and followed enrichment program. On the contrary, those who had not achieved KKM score, got warning and entered the remedial program. Keywords : learning, English language, laboratory.